Open Innovation in Medical and Pharmaceutical Research: A Literature Landscape Analysis - Yeung, Andy Wai Kan; Atanasov, Atanas G.; Sheridan, Helen; Klager, Elisabeth; Eibensteiner, Fabian; Völkl-Kernsock, Sabine; Kletecka-Pulker, Maria; Willschke, Harald; Schaden, Eva (Frontiers in Pharmacology, 2021)
Open innovation in medical and pharmaceutical research has grown steadily over the last decade. However, the performance of the published literature in terms of scientific impact and gain of social media attention remained largely unexplored. The scientific literature of open innovation was examined by means of bibliometric analyses to identify the most prolific authors, organizations, countries, journals, research areas, and recurring terms. By accessing Web of Science Core Collection and Altmetric electronic databases, citation-related and Altmetric data were evaluated. Public-private partnerships and a selection of newly introduced potential novel drugs introduced in the analyzed publications were identified. North America and Europe were the major literature contributors. Research outputs were mainly published in journals focused on business and economics, pharmacology and pharmacy, and engineering. Many pharmaceutical and biotechnological companies contributed to the analyzed publications, with higher mean citation counts and social media attention (Altmetric score) than non-industry papers. Public-private partnerships fostered financial support, sharing of expertise and intellectual property and research collaborations. In summary, open innovation might serve as a powerful strategy to both benefit the involved industry entities as well as to accelerate the development of solutions and products for the betterment of human health.